Questioni vecchie e nuove su status filiationis e PMA. Breve cronistroria (TEST BioLaw Journal - Rivista di BioDiritto, 2014)
The aim of this study is to examine the evolution of status issues in the regulation before and after law no. 40/2004, highlighting the critical points. It will try to demonstrate the aim, but also the limits of the principle of responsibility.
Keywords: denying paternity; embryosâ€™ mixâ€up; assisted reproduction with gamete donation; homologous fertilisation; surrogate mothers